Ocular pigmentation in humans, great apes, and gibbons is not suggestive of communicative functions - Kai R. Caspar (Nature Portfolio, 2021)
Abstract Pigmentation patterns of the visible part of the eyeball, encompassing the iris and portions of the sclera, have been discussed to be linked to social cognition in primates. The cooperative eye hypothesis suggests the white sclera of humans to be a derived adaptive trait that enhances eye-mediated communication. Here, we provide a comparative analysis of ocular pigmentation patterns in 15 species of hominoids (humans, great apes & gibbons) that show marked differences in social cognition and quantify scleral exposure at the genus level. Our data reveals a continuum of eye pigmentation traits in hominoids which does not align with the complexity of gaze-mediated communication in the studied taxa. Gibbons display darker eyes than great apes and expose less sclera. Iridoscleral contrasts in orangutans and gorillas approach the human condition but differ between congeneric species. Contrary to recent discussions, we found chimpanzee eyes to exhibit a cryptic coloration scheme that resembles gibbons more than other apes. We reevaluate the evidence for links between social cognition and eye pigmentation in primates, concluding that the cooperative eye hypothesis cannot explain the patterns observed. Differences in scleral pigmentation between great apes and humans are gradual and might have arisen via genetic drift and sexual selection.